O novo padrão de desenvolvimento agroindustrial e a atuação das cooperativas agropecuárias no Paraná - Fajardo, Sergio [UNESP] (My University, 2006)
This article aims at discussing the transformations in the cooperativist rural sector in the state of Paraná since 1970. Considerable active agents in the process of modernization in the agriculture from Paraná, the cooperatives developed also an important role in the productive restructuralization in the State of Paraná, when they started the agroindustrial activities. The verticalization represented a big growth of the cooperatives that act in the rural area, but it also implied in a redirection of the cooperatives' strategies, that started acting in an extremely competitive market.
The new pattern of the agroindustrial development and the cooperatives in the Paraná state
Keywords: Agroindustrial section; Economy from paraná; Paraná cooperatives; agroindustry; cooperative sector; industrial development; rural area; Brazil; Parana; South America